Influenced ShÅmikigen on Japanese Consumer Behaviour - Agusta, Nisia Nur Dwi (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
Food date labelling is an essential concern for Japanese society which results in a culture of homogeneous and homogeneous consumption behaviour in Japan. This culture of consumption behaviour is analysed using a food ethics approach, which is inseparable from the role of social actors and institutions in society, in this case, fovernment. This article used qualitative methods with literature studies, showing that high literacy skills make it easier for Japanese people to have the same food ethics beliefs that You should leave 8 mm of space above the abstract and 10 mm after the eventually become entrenched. However, on the other hand, it creates another problem called food waste.